KAJIAN HISTOKIMIA DISTRIBUSI KARBOHIDRAT PADA TESTIS SAPI SUMBA ONGOLE (Bos indicus) - Amalo, Filphin Adolfin; Maha, Inggrid; Nitbani, Heny; Gaina, Cynthia (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2022)
Testis is the male reproductive organ that performs both endocrine and exocrine functions. This study aimed to determine the distribution of carbohydrates in the testis of sumba ongole cattle. The sample consisted of six testis were collected from East Sumba Slaughter House, fixed in formalin 10 %, processed histologically, and continued with AB pH 2,5 - PAS staining. The result showed a weak alcian blue intensity (+) in the tunica albuginea and moderate intensity (++) in the interstitial connective tissue, basement membrane, and connective tissue in the lumen of the seminiferous tubules. A strong intensity (+++) to PAS staining was seen in spermatogonia, spermatocytes, and myoid cells. Spermatids, spermatozoa, and sertoli cells showed a negative reaction (-). In the intertubular area, Leydig cells and fibroblasts showed a strong PAS reaction (+++), connective tissue showed a moderate reaction (++). The intensity of the weak reaction (+) is indicated by the basement membrane of the seminiferous tubules. The variation in the distribution of acidic and neutral carbohydrates in the testis of sumba ongole cattle is correlated with the proliferation of different cell types and steroidogenic activity at various stages of testicular development.